2020
DOI: 10.1016/j.psj.2019.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of Withania somnifera root extract in Escherichia coli–infected broilers

Abstract: The present study was undertaken to investigate the effect of aqueous Withania somnifera root ( WSR ) extract in broiler chicks experimentally infected with Escherichia coli O78 @ 10 7 CFU/0.5 ml intraperitoneally. Clinical signs and mortality due to colibacillosis observed in infected chicks were mild and lasted for short duration in WSR extract supplemented group as compared with the nonsupplemented group. A significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
12
8
0
Order By: Relevance
“…This result was confirmed by degenerative changes in the renal epithelium, slight degeneration of some renal tubules and hemorrhage in the interstitial tissue of infected group. Our results agree with Kumari et al [44,45].…”
Section: ________________________________________________supporting
confidence: 94%
See 3 more Smart Citations
“…This result was confirmed by degenerative changes in the renal epithelium, slight degeneration of some renal tubules and hemorrhage in the interstitial tissue of infected group. Our results agree with Kumari et al [44,45].…”
Section: ________________________________________________supporting
confidence: 94%
“…Biochemical studies revealed significant increase in the serum AST and ALT activity of the infected group. Similar results have been reported by Kumari et al [44,45] who worked on E. coli infection in broiler chickens. These increases could be attributed to hepatocellular damage.…”
Section: ________________________________________________supporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, in Egypt, Ramadan et al [ 17 ] demonstrated the existence of shared antimicrobial resistances between E. coli isolated from retail chicken carcasses and humans. Recently, there has been an increasing interest in replacing antibiotics with an alternative variety of natural products, such as medicinal plants [ 15 , 18 ] and probiotics [ 18 , 19 , 20 , 21 ], to ameliorate poultry antioxidant status, immune response, growth performance and egg production.…”
Section: Introductionmentioning
confidence: 99%